Invitro Screening of Antifungal Activity of Rhizospheric Bacteria and Possible Role of Chitinase in Antifungal Activity - Devkota, Hari K; Maharjan, Bijaya L; Baral, Bikash; Singh, Anjana; Yami, Kayo D (Nepal Journal of Science and Technology, 2012)
The use of biocontrol agents is becoming an increasingly important alternative to chemical crop protection against weeds, insects and plant diseases in the field of agriculture. The success of biocontrol and yield increase depends on the nature of antagonistic properties and mechanisms of action of the biocontrol agent against the phytopathogens. In this study, 103 macroscopically different bacterial isolates (62 from Kirtipur and 41 from Khumaltar) from 21 different rhizosphere soil samples (11 from Kirtipur and 10 from Khumaltar) were screened for antagonism against five fungal phytopathogens, viz, Fusarium oxysporum, Alternaria solani, Sclerotium rolfsii, Exserohilum turcicum and Phytophthora infestans by dual culture technique on Potato dextrose agar. Out of 18 different active isolates two of them showed the chitinolytic potential and the most active fungal antagonist was identified as Bacillus subtilis on the basis of colonial, morphological, physiological and biochemical characteristics based on Bergey’s Manual of systemic bacteriology. The isolate produced maximum chitinase in colloidal chitin broth at pH7 and temperature 37oC after four days of inoculation. The corresponding culture filtrate supposed to contain chitinase showed maximum % inhibition of 53.29% with Fusarium oxysporum and no inhibition to Phytophthora infestans in agar well diffusion assay. Furthermore, chitinase was best fractionated at 40% ammonium sulphate salt fractionation which has almost similar inhibition potential as the crude culture filtrate. The 40% salt fraction of the enzyme showed the maximum chitinolytic potential at pH8 and temperature 40oC. Among the phytopathogens tested, sensitivity of Bacillus subtilis to fungi containing chitin on their cell wall demonstrates the possible role of chitinase in the antifungal activity. DOI: http://dx.doi.org/10.3126/njst.v12i0.6517 Nepal Journal of Science and Technology 12 (2011) 304-311